High-temperature oxidation behavior of Ni-11Fe-10Cu alloy: Growth of a protective oxide scale. (November 2016) - Cheng, Xinhua; Fan, Lei; Yin, Huayi; Liu, Li; Du, Kaifa; Wang, Dihua
Graphical abstract: Highlights: High-temperature oxidation behavior of Ni-11Fe-10Cu alloy in air. A three-layer oxide scale of CuO, NiFe2 O4 and NiO and a thin copper layer formed on the alloy surface. The growth mechanism of oxide scale was analyzed by both thermodynamics and diffusion theory. The effect of material preparation process of casting and forging on the oxidation was investigated. Abstract: The oxidation of Ni-11Fe-10Cu alloys in air at high temperature was investigated. A parabolic kinetics was found at 750 °C and a linear kinetics was shown at 850 and 950 °C. The oxide scale formed at 750 °C is compact and coherent possessing triplex oxide layers, i.e., a CuO external layer, a NiFe2 O4 middle layer, and a NiO inner layer. A thin copper-rich layer sits between the scale and alloy substrate, functioning as a barrier for iron and nickel diffusing outwards from the alloy substrate and oxygen ion diffusing inwards. The growth mechanism of the multi-layer oxide scale was discussed.